Queueing and channel access delay analysis in in-band full-duplex wireless networks - Yanjing Sun; Haiwei Zuo; Yan Chen; Bin Wang (International Journal of Distributed Sensor Networks)
In-band full-duplex wireless communication, which supports a node to transmit and receive simultaneously in the same frequency band, is receiving growing interest. The latency of packets in an in-band full-duplex wireless network can be significantly lowered by employing effective medium access control. However, queue delay is not considered in current delay performance analysis works, which do not describe the delay of a packet from generation to reception or analyze the ability to support real-time traffic. In this article, an easily expandable three-way handshaking in-band full-duplex medium access control mechanism is proposed, and both queueing delay and access delay are analyzed. Based on an M/G/1 queuing model, the system delay of in-band full-duplex access point from the packet coming to the queue, to its successful reception by the destination user, is provided. Simulation results show that compared with half-duplex access point, in-band full-duplex access point performs excellent low latency.